Regional Analgesia Following Caesarean Section: New Kid and a Block?. Issue 4 (21st December 2022) - Kearsley, R.; Campbell, J.P.
Abstract : ( Anaesthesia . 2022;77:376–379. doi: 10.1111/anae.15646) It is anticipated by the World Health Organization (WHO) that the rapidly rising global trend for cesarean delivery (CD) will increase from 21.1% in 2022 to 28.5% in 2030, accounting for 38 million CD per year. Mitigating pain after CD is an important focus, as high pain scores can develop into chronic pain for the mother, prevent bonding with and caring for the infant, and may exacerbate postpartum depression risk.